Avaliação da APS: uma análise da coordenação da atenção nos municípios do interior do RS - Bandeira, Danieli (2016)
The Primary Health Care (PHC) is shown as a strategic space for the exercise of management and evaluation in health. In this scenario, the coordination of care is considered one of its four key attributes. This is understood by the ability to ensure continuity of care in the service network and the identification of issues that are addressed in other levels of the network. In this sense, this research aims to evaluate the PHC quality in the municipalities of the 4ªCRS / RS by checking the coordination of care, by applying the PCATool (Brazil) at the top-level health professionals and service users health, ≥ 18 years and whose access was not the first. This is a quantitative approach to research with cross-sectional design. Data collection was carried out from February to August 2015, the PHC services in the municipalities of the 4th CRS / RS / BR. The study population included 1,071 adults and 203 professionals working in PHC. Data collection was conducted through interviews by applying the research protocol (demographic questionnaire and PCATool-Brazil version Adult and Professional) and was held in a computerized manner. Data were collected using Epi Info 7.0 program and automatically extracted for notebooks. The analysis was performed using the Statistical Package for Social Sciences (SPSS) version 19.0 for Windows. scores were the Attention Coordination attribute. Please note that the ethical aspects of research involving human beings were respected, according to the National Health Council Resolution 422/12. The results revealed by this study show that the Warning Coordination attribute was evaluated as satisfactory, that is, obtained a Top rated in dimensions Integration and Care Information System, both in the adult version and the professional version. In the adult version scores in dimension Care Integration were: the Basic Health Units (BHU) 6.66 (6.28 to 7.03), in the Family Health Strategy (ESF) 6.34 (5.94 -6.73) and in mixed UBS 6.87 (6.30 to 7.43); the scores in the dimension Information System were: the UBS 7.22 (7.02 to 7.41), the ESF 7.09 (6.88 to 7.29) and in mixed UBS 7.26 (6.94 -7.57). In the professional version scores in dimension Care Integration were: the UBS 6.34 (5.79 to 6.88), the ESF 6.41 (6.01 to 6.80) and in mixed UBS 6.74 ( 6.24 to 7.23); the scores in the dimension Information System were: the UBS 8.84 (8.22 to 9.45), the ESF 8.77 (8.40 to 9.13) and in mixed UBS 8.54 (8.03 -9.04). The results presented in this study have important implications for the evaluated services and also for public policy attention to health of the 32 municipalities that make up the two health regions studied. In addition to strengthening the development of evaluation studies in order to improve the quality of PHC and coordination of care.